Measurement of Supply Chain Management Performance in Sago Flour Business Using the Supply Chain Operation Reference (SCOR) Method to Increase SME Productivity: Pengukuran Kinerja Supply Chain Management pada Usaha Tepung Sagu dengan Menggunakan Metode Supply Chain Operation Reference (SCOR) untuk Meningkatkan Produktivitas UKM - Juwairiah, Juwairiah; Handayani, Nurlaila; Nadya, Yusri (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2023)
Sago Flour UKM Pak Hamid is one of the players in the sago flour industry in Meunaro Village, Peureulak District, East Aceh Regency. The problems experienced were the difficulty of obtaining sago raw materials in the nearest area, delays in sago raw materials from the time of ordering, and the weather often rained in certain months so that the river water was cloudy. The purpose of the following experiment is to see what aspects are the influence of management capacity on Peureulak Sago Flour SMEs, calculate supply chain processing capacity in Sago Flour SMEs using supply techniques, find out the proposed supply chain management performance restoration. The method used means method (SCOR) which is a reference example of supply chain management activities based on procedures which are divided into 5 systems, namely planning, sourcing, creating, delivering, and returning. The results of this study share the final value of supply chain performance in sago flour SMEs is 56.9117 in the average category (Average), then the proposed improvements that can be made by sago flour SMEs in plan activities by adding suppliers to meet the shortage of raw materials, sago flour SMEs are expected to have their own sago stem plants, source by discussing business rules with suppliers, make by adding some new employees, deliver by improving good communication with consumers, improve service to consumers, and make tubs for clean water supplies, return by throwing water when the flour has settled and replaces it with clean water, wash the dregs filter cloth.